2021
DOI: 10.1021/acs.jnatprod.0c00869
|View full text |Cite|
|
Sign up to set email alerts
|

Phytochemical Profiling and Biological Activity of the Australian Carnivorous Plant, Drosera magna

Abstract: Phytochemical profiling was undertaken on the crude extracts of Drosera magna to determine the nature of the chemical constituents present. In total, three new flavonol diglycosides (1–3), one new flavan-3-ol glycoside (4), and 12 previously reported compounds of the flavonol (5, 9), flavan-3-ol (15), flavanone (8), 1,4-napthoquinone (6, 7, 13, 14), 2,3-dehydroxynapthalene-1,4-dione (10–12), and phenolic acid (16) structure classes were isolated and identified. Compounds 1–9, 13, 17, and 18 were assessed for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…In this study, thirty-four compounds ( 1 – 34 ) were isolated from the aerial parts of F. dentatoalata via extensive column chromatography. These were identified as apigenin ( 1 ) ( Ha et al, 2012 ), isovitexin ( 2 ) ( Jayasinghe et al, 2004 ), kaempferol ( 3 ) ( Fukai and Nomura, 1988 ), afzelin ( 4 ) ( Xu et al, 2009 ), astragalin ( 5 ) ( Otsuka et al, 1989 ), kaempferol-3-​rutinoside ( 6 ) ( de Sa de Sousa Nogueira et al, 2013 ), luteolin ( 7 ) ( Zhang et al, 2015 ), quercetin ( 8 ) ( Lesjak et al, 2018 ), guaijaverin ( 9 ) ( Yoshida et al, 1992 ), hyperoside ( 10 ) ( Isaza et al, 2001 ), tamarixetin-​3-​rhamnoside ( 11 ) ( Norman et al, 2021 ), quercitrin ( 12 ) ( Chen et al, 2008 ), isoquercitrin ( 13 ) ( Jin et al, 2009 ), rutin ( 14 ) ( Kazuma et al, 2003 ), quercetin-​3-​ O -​robinoside ( 15 ) ( Dossou et al, 2021 ), myricetin ( 16 ) ( Zhang et al, 2004 ), myricitrin ( 17 ) ( Kil et al, 2019 ), (+)-​catechin ( 18 ) ( Foo et al, 1997 ), (-)-​epicatechin ( 19 ) ( Lin and Lee, 2010 ), zizyflavoside B ( 20 ) ( Yang et al, 2020 ), emodin ( 21 ) ( Meselhy, 2003 ), physcion ( 22 ) ( Jo et al, 2011 ), glucofrangulin A ( 23 ) ( Bezabih and Abegaz, 1998 ), torachrysone-​8-​ O -​β-​D-​glucoside ( 24 ) ( Zhao et al, 2017 ), polydatin ( 25 ) ( Yi et al, 2020 ), tetrahydroxystilbene​-​2-​ O -​β-​D-​glucoside ( 26 ) ( Tsai et al, 2018 ), ( E )-2,3,5,4′-tetrahydroxystilbene-2- O -(2″- O -galloyl)-β-D-glucoside ( 27 ) ( Nguyen et al, 2020 ), protocatechuic acid ( 28 ) ( Meng et al, 2021b ), gallic acid ( 29 ) ( Chen et al, 2021 ), lapathoside B ( 30 ) ( Takasaki et al, 2001 ), vanicoside B ( 31 ) ( Kumagai et al, 2005 ), lapathoside A ( 32 ) ( Takasaki et al, 2001 ), smilaside J ( 33 ) ( Zhang et al, 2008 ), and smilaside G ( 34 ) ( Takasaki et al, ...…”
Section: Resultsmentioning
confidence: 99%
“…In this study, thirty-four compounds ( 1 – 34 ) were isolated from the aerial parts of F. dentatoalata via extensive column chromatography. These were identified as apigenin ( 1 ) ( Ha et al, 2012 ), isovitexin ( 2 ) ( Jayasinghe et al, 2004 ), kaempferol ( 3 ) ( Fukai and Nomura, 1988 ), afzelin ( 4 ) ( Xu et al, 2009 ), astragalin ( 5 ) ( Otsuka et al, 1989 ), kaempferol-3-​rutinoside ( 6 ) ( de Sa de Sousa Nogueira et al, 2013 ), luteolin ( 7 ) ( Zhang et al, 2015 ), quercetin ( 8 ) ( Lesjak et al, 2018 ), guaijaverin ( 9 ) ( Yoshida et al, 1992 ), hyperoside ( 10 ) ( Isaza et al, 2001 ), tamarixetin-​3-​rhamnoside ( 11 ) ( Norman et al, 2021 ), quercitrin ( 12 ) ( Chen et al, 2008 ), isoquercitrin ( 13 ) ( Jin et al, 2009 ), rutin ( 14 ) ( Kazuma et al, 2003 ), quercetin-​3-​ O -​robinoside ( 15 ) ( Dossou et al, 2021 ), myricetin ( 16 ) ( Zhang et al, 2004 ), myricitrin ( 17 ) ( Kil et al, 2019 ), (+)-​catechin ( 18 ) ( Foo et al, 1997 ), (-)-​epicatechin ( 19 ) ( Lin and Lee, 2010 ), zizyflavoside B ( 20 ) ( Yang et al, 2020 ), emodin ( 21 ) ( Meselhy, 2003 ), physcion ( 22 ) ( Jo et al, 2011 ), glucofrangulin A ( 23 ) ( Bezabih and Abegaz, 1998 ), torachrysone-​8-​ O -​β-​D-​glucoside ( 24 ) ( Zhao et al, 2017 ), polydatin ( 25 ) ( Yi et al, 2020 ), tetrahydroxystilbene​-​2-​ O -​β-​D-​glucoside ( 26 ) ( Tsai et al, 2018 ), ( E )-2,3,5,4′-tetrahydroxystilbene-2- O -(2″- O -galloyl)-β-D-glucoside ( 27 ) ( Nguyen et al, 2020 ), protocatechuic acid ( 28 ) ( Meng et al, 2021b ), gallic acid ( 29 ) ( Chen et al, 2021 ), lapathoside B ( 30 ) ( Takasaki et al, 2001 ), vanicoside B ( 31 ) ( Kumagai et al, 2005 ), lapathoside A ( 32 ) ( Takasaki et al, 2001 ), smilaside J ( 33 ) ( Zhang et al, 2008 ), and smilaside G ( 34 ) ( Takasaki et al, ...…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 98–101 were isolated from the leaves of Drosera magna . Compounds 98–100 are flavone diglycosides, while compound 101 is a flavan glycoside [ 49 ]. Compounds 102–104 were isolated from the roots of Phyllanthus acidus .…”
Section: Isolation Of Novel Flavonoids Isoflavonoids and Neoflavonoidsmentioning
confidence: 99%
“…Compounds 98 and 99 showed no anthelmintic activity against exsheathed third-stage larvae and fourth-stage larvae of H. contortus . The results indicated that the acetyl groups in compounds 99–101 were deactivating [ 49 ].…”
Section: Bioactivities Of Flavonoids Isoflavonoids and Neoflavonoidsmentioning
confidence: 99%
“…114 A series of diterpene acylphloroglucinols from the male fern Dryopteris wallichiana (Dryopteridaceae) were reported to exhibit in vitro activity against N. brasiliensis L4 larvae, namely wallichins A (3.99) (LD 50 The hydroxy-droserone 1,4-napthoquinone 3.107 isolated from the Western Australia carnivorous plant Drosera magna (Droseraceae) inhibited motility of H. contortus L4 larvae (EC 27 22 mg mL −1 aer 72 h) and induced an abnormal phenotype at >11 mg mL −1 . 118,119 The chlorophyll breakdown product phaeophorbide a (3.108), found in the leaves of the hog plum Spondias mombin L. (Anacardiaceae), was active against the roundworm H. placei (LC 50…”
Section: Miscellaneousmentioning
confidence: 99%
“…The hydroxy-droserone 1,4-napthoquinone 3.107 isolated from the Western Australia carnivorous plant Drosera magna (Droseraceae) inhibited motility of H. contortus L4 larvae (EC 27 22 μg mL −1 after 72 h) and induced an abnormal phenotype at >11 μg mL −1 . 118,119…”
Section: Plantsmentioning
confidence: 99%